Membedah Kesalahan Bahasa Indonesia Dalam Caption Dan Komentar di Platform Media Sosial Instagram - Cici Cahyani; Bintang Nurheni; Elisa Br Lumban Tobing (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This study delves into the usage of Indonesian language on the social media platform Instagram, with a particular focus on identifying and analyzing the prevalent errors and misunderstandings that arise. Employing a descriptive qualitative research methodology, the study examines user-generated comments and captions. The findings reveal that users frequently commit spelling mistakes on basic words, including capitalization, punctuation, and word separation. Additionally, inappropriate word choices and grammatical errors are common among users. Furthermore, the mixing of Indonesian with slang, English, and local dialects contributes to confusion and communication barriers. Overall, the study highlights the suboptimal usage of Indonesian on Instagram, emphasizing the need for enhanced language proficiency and effective communication strategies.